EVALUASI KANDUNGAN BAHAN KERING, BAHAN ORGANIK DAN PROTEIN KASAR PELEPAH SAWIT FERMENTASI DENGAN PENAMBAHAN SUMBER KARBOHIDRAT - Tri Astuti; M N Rofiq; Nurhaita Nurhaita (State Islamic University of Sultan Syarif Kasim Riau, 2017)
This research was aimed to evaluate the content of dry matter, organic matter and crude protein of palm oil fronds as an alternative feed substitution of native grass, which was enhanced through fermentation biotechnological innovation with the addition of carbohydrate soluble. Fermentation palm oil frond done using local microorganisms resources rumen content andLactobacillus. The experimental design used was factorial on complete randomized design 2x3 with 3 replication each treatment. Factor A were the source of inoculums fermentation, A1=. lactobacillus, A2= local microorganisms resources rumen content. Factor B were the source of soluble carbohydrates where B1 = without a carbohydrates, rice B2 = e bran, B3 = tapioca starch. Parameters measured were content of dry matter, organic matter and crude protein of palm oil fronds. The results of this research showed that no interaction effect between the source of microorganisms with carbohydrates, and the treatment had no effect (P > 0.05) on dry matter content. No effect Factor A for all parameters while the factors B Influential were significantly (P < 0.01) on the content of organic matter and crude protein. The highest crude protein content in the fermented palm oil fronds with a source of carbohydrates from rice bran (6.55%)